2021
DOI: 10.2147/ijgm.s294294
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Practice and Food Poisoning Associated Factors Among Parents in Bench-Sheko Zone, Southwest Ethiopia

Abstract: Background Food poisoning is a food borne disease, mainly resulting from ingestion of food that contains a toxin, chemical or infectious microorganisms like bacteria, virus, parasite, or prion. On the other hand, avoiding food contamination during preparing and feeding is a key factor for reducing the prevalence of food poisoning. This study aimed to assess the knowledge, attitude, self-reported practice and food poisoning associated factors among parents in the selected health centers of Bench-Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Meanwhile, employed mothers also significantly had higher satisfactory hygienic practices in relation to the prevention of food poisoning (Zyoud et al, 2019). Similar findings were also reported among parents in Ethiopia (Mekonnen et al, 2021).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Meanwhile, employed mothers also significantly had higher satisfactory hygienic practices in relation to the prevention of food poisoning (Zyoud et al, 2019). Similar findings were also reported among parents in Ethiopia (Mekonnen et al, 2021).…”
Section: Introductionsupporting
confidence: 87%
“…Many studies have also identified associated factors of hygiene related knowledge, attitude and practice among parents and caregivers, from the perspectives of food hygiene or food poisoning (Mekonnen et al, 2021; Zyoud et al, 2019) in general, with lacking evidence among the indigenous community. In a study conducted among parents in Palestine, those with a higher education level and who live in a city were found to have significantly higher hygiene knowledge scores, with hygiene attitude that was also improved as educational level increased and income level increased (Zyoud et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies published on food poisoning showed that many factors influence food safety knowledge, attitudes, and practice, including age, gender, residency, and education (Mekonnen et al, 2021; Mshelia et al, 2022; Shati et al, 2021; Yemane & Tamene, 2022). Older age, along with an increased length of practice, is associated with increased knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Females tend to have a better attitude than males, as is reflected in a study about postgraduate students in a public university in Selangor, Malaysia, 19 and research conducted among parents in the Bench-Sheko region, Southwestern Ethiopia. 25 Meanwhile, research results on students at Majmaah University show no such relationship. 18 Our research also revealed that respondents who had engaged in courses or subjects covering FP demonstrated better attitudes, aligning with findings from a study conducted on students in Bangladesh.…”
Section: Attitude About Preventive Food Poisoning and Its Associated ...mentioning
confidence: 99%
“…Similar to the research results on veterinary students at Trakia University, Bulgaria, 23 our study shows that females are more likely to have good FP prevention practices than males, supporting the findings of studies conducted in Palestine, 8 Bangladesh, 21 and Southwestern Ethiopia. 25 This can be attributed to females' often food-processing activities and preparing and providing meals for their families. Consequently, they may have a stronger motivation to prevent FP.…”
Section: Practices About Preventive Food Poisoning and Its Associated...mentioning
confidence: 99%